(untitled) (Bioscience Journal, 2016)
The objective was to evaluate the genetic variability among pepper accessions al the physical and chemical characteristics of fruit. Pepper accesses are from the Germplasm Bank at the Federal University of Uberlandia - Monte Carmelo Campus (Universidade Federal de Uberlândia-UFU, Campus Monte Carmelo, MG, Brazil). The experiment was conducted from November 2013 to March 2014 at UFU’s Experimental Station on the Monte Carmelo campus, MG, Brazil. The statistical design consisted of randomized blocks with 47 treatments and four replications. Multivariate analyzes were performed for quantitative traits in 47 pepper access by principal component analysis. Means were compared by Scott-Knott test (Î± = 0.05). Mature fruits were collected 120 days after transplant and used to determine titratable acidity (TA), total soluble solids (SS), pH and SS/TA. There was genetic variability among accessions. The 47 accessions showed high soluble solids content of 9.08 ° Brix, acidity of 0.22, pH of 5.50 and an SS/TA ratio of 33.8. This last characteristic is of great importance in the food processing industry. UFU accession 28 has high levels of SS and TA and is therefore a candidate for Pepper breeding programs that target the needs of the food processing industry.